Increased duodenal iron uptake and transfer in a rat model of chronic hypoxia is accompanied by reduced hepcidin expression. Issue 10 (24th May 2005) - Leung, P S; Srai, S K; Mascarenhas, M; Churchill, L J; Debnam, E S
Abstract : Background: Despite the requirement for increased iron delivery for erythropoiesis during hypoxia, there is very little information on how duodenal iron uptake and its transfer to the blood adapts to this condition. Aims: To assess the effects of 30 days of chronic hypoxia in rats on luminal iron uptake and transfer of the metal to blood, together with gene expression of hepcidin, a proposed negative regulator of iron transport. Methods: 59-Fe uptake by isolated duodenum and its transfer to blood by in vivo duodenal segments was measured after exposure of rats to room air or 10% oxygen for four weeks. Liver hepcidin expression was measured by real time reverse transcription-polymerase chain reaction. The effects of hypoxia on hepcidin gene expression by HepG2 cells was also determined. Results: Hypoxia did not affect villus length but enhanced (+192.6%) luminal iron uptake by increasing the rate of uptake by all enterocytes, particularly those on the upper villus. Hypoxia promoted iron transfer to the blood but reduced mucosal iron accumulation in vivo by 66.7%. Hypoxia reduced expression of hepcidin mRNA in both rat liver and HepG2 cells. Conclusions: Prolonged hypoxia enhances iron transport from duodenal lumen to blood but the process is unable to fully meet the iron requirement for increased erythropoiesis. Reduced secretion of hepcidin may be pivotal to the changes in iron absorption. The processes responsible for suppression of hepcidin expression are unknown but are likely to involve a direct effect of hypoxia on hepatocytes.